Hedonisme Spiritual pada Tayangan Religi: Analisis Wacana Kritis Program “Islam Itu Indah" di TransTV - Puji Hariyanti (Jurnal Komunikasi, 2011)
The television through religious program wanted to show that religion doctrine could be packed as entertaining program. Then, it came to us as an easy, simple, and brief lesson. But in practice, it made Moslems became individualistic. They concerned only in individual piety, without thinking and trying more to solve complex social problem. This study focused in how the textual tendency of spiritual hedonism discourse is was shown in the text of the religious program “Islam Itu Indah” in TransTV. Results showed that the passion of religiousness in a modern people that practice hedonism and materialism as a life style was increasing. Besides, commercialization of religion then came in the form of spiritual hedonism—a spiritual practice that aimed to be enjoyed and not to be taken seriously. Religion was shown in a stage of popular culture only just as the symbolic of piety.